Methane pumping by rapidly refreezing lead ice in the ice-covered Arctic Ocean - Damm, Ellen; Thoms, Silke; Angelopoulos, Michael; Von Albedyll, Luisa; Rinke, Annette; Haas, Christian (Frontiers in Earth Science, 2024)
If and how the sea ice cycle drives the methane cycle in the high Arctic is an open question and crucial to improving source/sink balances. This study presents new insights into the effects of strong and fast freezing on the physical–chemical properties of ice and offers implications for methane fluxes into and out of newly formed lead ice. During the 2019–2020 transpolar drift of the Multidisciplinary Drifting Observatory for the Study of Arctic Climate (MOSAiC), we took weekly samples of growing lead ice and underlying seawater at the same site between January and March 2020. We analyzed concentrations and stable carbon isotopic signatures (δ13C–CH4) of methane and calculated methane solubility capacities (MSC) and saturation levels in both environments. During the first month, intense cooling resulted in the growth of two-thirds of the final ice thickness. In the second month, ice growth speed decreased by 50%. Both growth phases, disentangled, exposed different freeze impacts on methane pathways. The fast freeze caused strong brine entrapment, keeping the newly formed lead ice permeable for 2 weeks. These physical conditions activated a methane pump. An increased MSC induced methane uptake at the air–ice interface, and the still-open brine channels provided top-down transport to the ocean interface with brine drainage. When the subsurface layer became impermeable, the top-down pumping stopped, but the ongoing uptake induced a methane excess on top. During the second growth phase, methane exchange exclusively continued at the ice–ocean interface. The shift in the relative abundance of the 12C and 13C isotopes between lead ice and seawater toward a 13C-enrichment in seawater reveals brine drainage as the main pathway releasing methane from aging lead ice. We conclude that in winter, refrozen leads temporarily function as active sinks for atmospheric methane and postulate that the relevance of this process may even increase when the Arctic fully transitions into a seasonally ice-covered ocean when leads may be more abundant. To highlight the relevance of methane in-gassing at the air–ice interface as a potential but still unconsidered pathway, we include estimates of the occurrence and frequency of young lead ice from satellite observations of leads during MOSAiC.